Sense-making of Digital Literacy for Future Education Era: A Literature Review - Widya Karmila Sari Achmad; Unga Utami (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
Technological sophistication that continues to develop contributes and is also integrated in education and learning. Conventional education and learning are shifting towards digital technology-based learning. Digital-based learning must undoubtedly be accompanied by skills and mastery of digital technology. Thus, this paper aims to describe and represent the sense-making elementary school students need regarding digital literacy to realize education in the future era. The method in this writing was a literature review by reviewing the relevant literature with the topic of discussion. The results revealed that the sense-making of education actors is the basic capital in digital-based learning. Therefore, the position of digital technology and digital literacy in education is central to realizing the success of education in the future era. Finally, the recommendations in this paper include (1) the need for regular training or programs related to sense-making of digital literacy so that education in the future era can be carried out optimally, effectively, and efficiently, and (2) further study and analysis are required in mapping the education system related to educational needs as a result of the impact of COVID-19 and education in the industrial revolution 4.0 era in the future.